The first person - Sword, Helen (Teaching and Learning Inquiry, 2019)
In this playful meditation on academic pronouns, I report on my research findings from three separate studies: a 2007 analysis of pronoun usage patterns in recent higher education articles; a 2017 analysis of pronoun usage patterns in Teaching and Learning Inquiry since the founding of the journal in 2013; and an updated 2017 analysis of the same five higher education journals examined a decade earlier. You may be surprised by the results. However, we are not inclined to reveal the whole story here in the abstract. It is the conviction of the author that the present article must be read in its entirety in order to be fully appreciated.